2007
DOI: 10.1542/peds.2006-1107
|View full text |Cite
|
Sign up to set email alerts
|

Pain Reduction During Pediatric Immunizations: Evidence-Based Review and Recommendations

Abstract: The pain associated with immunizations is a source of anxiety and distress for the children receiving the immunizations, their parents, and the providers who must administer them. Preparation of the child before the procedure seems to reduce anxiety and subsequent pain. The limited available data suggest that intramuscular administration of immunizations should occur in the vastus lateralis (anterolateral thigh) for children <18 months of age and in the deltoid (upper arm) for those >36 months of age. Controve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
200
0
20

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(238 citation statements)
references
References 128 publications
(110 reference statements)
4
200
0
20
Order By: Relevance
“…7 In children, parental reassurance, criticism and apologizing have been shown to be associated with higher expressed children's distress. 53,71 The types of pain behaviors observed in others throughout life would be expected to have a cumulative impact on the repertoire of behaviors available to observers when confronted with comparable painful situations.…”
Section: Modulation By Characteristics In the Environmentmentioning
confidence: 99%
“…7 In children, parental reassurance, criticism and apologizing have been shown to be associated with higher expressed children's distress. 53,71 The types of pain behaviors observed in others throughout life would be expected to have a cumulative impact on the repertoire of behaviors available to observers when confronted with comparable painful situations.…”
Section: Modulation By Characteristics In the Environmentmentioning
confidence: 99%
“…2 Literatürde, başparmak ve işaret parmağı arasında kalan cilt bölgesini düz ve gergin tutarak femurun uzun eksenine enjektörü 90 o uygulamanın aşılara bağlı sistemik ve lokal reaksiyonlara daha az neden olduğu, enjeksiyon uygulanan bölgedeki cildin gerilmesinin sadece doğru iğne yerleştirmesini sağlamadığı, aynı zamanda ağrı hissini azaltan ağrı yönetim stratejisi olarak da kullanılabileceği belirtilmektedir. 12 Yenidoğanlar için güvenli ilaç hacmi uygulayabilmek için küçük enjektörlerin (0,5 mL vb) kullanılması tercih edilmelidir. İlaç cam ampulden çekilecek ise, uygulama sırasında iğne ucu değiştirilmelidir.…”
Section: Kullanilacak İğneni̇n Uzunluğuunclassified
“…Böylece cam parçacıkları ile bebeğin potansiyel yaralanma riski engellenecektir. 5,12,13 Yapılan randomize kontrollü bir çalışmada, 59 makrozomik yenidoğandan (doğum ağırlığı 4.000 g'dan fazla) 25 mm iğne ile aşılananlarda hepatit B aşısı sonrası oluşan antikor seviyesi, 16 mm iğne ile aşılanan yenidoğanlara göre belirgin olarak daha yüksek seviyelerde belirlenmiştir. Bu sonuç ile aşı-lama sırasında yeterince kas derinliğine ulaşılma-sının önemi ortaya konulmuştur.…”
Section: Kullanilacak İğneni̇n Uzunluğuunclassified
“…Before reaching the age of 6, they receive 20 or more immunizations, including polio, BCG, measles, and rubella vaccines, in Japan [1] [2]. As each immunization involves pain [3], insufficient pain management may result in future medical fear or pain [4]. Therefore, it is important to develop effective methods to reduce pain during immunization.…”
Section: Introductionmentioning
confidence: 99%
“…The latter include: musical interventions [5] [8], distraction using videos [5] [8], breathing techniques [5] [9], sucrose administration [8] [10], and positioning [10]. In a systematic review to examine the pain-relieving effect of music, it was shown to reduce pain and anxiety in children (aged 1 -18) when receiving medical care [11].…”
Section: Introductionmentioning
confidence: 99%